Pedagogical Practice in Teaching - Learning Mathematics in Secondary in School Level - Pokharel, Jagat Krishna (Rupantaran: A Multidisciplinary Journal, 2020)
This article reflects about the effective and concrete learning of mathematics with the help of self-devised innovative activities, worksheets, project experiments and teaching aids. The present research shows if maximum participation of students is ensured -either in the mathematics laboratory activities or class room interactive questioning sessions like that of quiz- is really joyful learning of the subject. `Learning by doing` is very effective methodology in teaching learning process as the experience gained meticulously (Krockover, 1997). It remains permanently fixed in the minds of the children. Thus, innovative teaching aids and projects of mathematic laboratory plays a vital role in the conceptualization process. Some researchers emphasize on the children`s experience of school education that must be linked with the life outside the school. It brings joyful experience in the learning. Keeping this in mind, several opportunities are provided to students to construct their systematic knowledge by engaging them in activities, experiment, field visits, discussion with peers and teachers, group works, brainstorming sessions, collecting information from different sources, inquiring, listening, thinking and so on. The students are encouraged and allowed to share and explain their ideas and ask, pose and frame questions. Appropriate innovative tools and techniques are applied depending on the situation and requirement.